The effectiveness of personal preventive measures against occupational contact dermatitis in healthcare workers: A systematic review - Khansa Maria Salsabila; Sri Awalia Febriana; Retna Siwi Padmawati; Retno Danarti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Healthcare workers (HCWs) embody the principles of hand hygiene and protective attire to support self- and patient safety, but the materials involved in this process are found to be offending agents. The incidence of occupational contact dermatitis (OCD) among HCWs keeps increasing. This review aimed to evaluate the effectiveness, investigate the outcome and clinical skin condition improvement with the implementation of primary preventive measures (PPM), specifically: barrier cream, emollient, moisturiser, gloves use, and education. All relevant literature about PPM against OCD among HCWs published between 1995 to 2020 was searched. The data search was performed using the PUBMED, Cochrane Library, and ScienceDirect databases. There were 16 studies comprised of 8 randomised controlled trials (RCTs), 7 clinical trials, and one comparative study. The study results showed that using barrier cream, moisturiser or emollient, gloves, and education were effective tools in reducing the number of clinical symptoms in cases of OCD. There was no significant difference in the effect between barrier cream use and moisturiser or emollient. The gloves were advised to be used non-latex gloves or powder-free latex gloves. Education was also observed to improve preventive behaviour among workers. The use of barrier cream, emollient, moisturiser, and gloves is recommended to be educated to ascertain the proper use of preventive measures, increase knowledge and awareness, and promote positive preventive behaviour.